Przekłady literatury słoweńskiej w Czechach i w Polsce w latach 1990—2006 / The translation of the Slovene Literature in the Czech Republic and in Poland in 1990—2006 - Jamnik, Tatjana (Przekłady Literatur Słowiańskich, 2009)
In this review od Czech and Polish translations of Slovene literature in the past 17 years, the author shows diversity and resemblance in the cultural image of Slovenia in the collective consciousness of the two nations. The chosen era of research falls into two distinct periods. In the first, before the year 2000, the translations lied solely on the shoulders of individual translators, members of the „old” generation. The second period is characterized with a great outburst of translated Slovene literature by the young generation of traslators. Trough analysis and comparison of translated books and translations published in journals and on the internet in the Czech Republic and Poland the author draws our attention to the discrepancy in the amount of translated publications. The article explores the possible reasons for these changes and differences in the field of Slovene translated literature in the two related countries.